Comparative Analysis of Strength and Test of Nodular Cast Iron and Aluminum Alloy Boxes for Metro Gearboxes - Hu Zhiqiang; Zhao Yuanyuan; Li Xi (Jixie chuandong)
A finite element simulation model is established for the gearbox body of 120B metro vehicle model in China. The fatigue strength, static strength and safe nose strength of aluminum alloy and nodular cast iron gearbox are calculated by the finite element method. The results show that the maximum equivalent stress of aluminum alloy case is larger than that of nodular cast iron, and the maximum difference ratio is 36.3%. The static strength and type test of aluminum alloy and nodular cast iron box are compared. The results show that the maximum stress of aluminum alloy case is greater than that of the ductile iron, and the difference ratio is 8.3%. The maximum sound power and vibration value of the aluminum alloy case are greater than that of the nodular cast iron case, but the average bearing temperature decreases by about 10 ℃. Although the strength of the aluminum alloy case is weaker than that of the nodular cast iron case, the overall factor of safety of the aluminum alloy case is higher than that of the nodular cast iron case, which can still meet the service life of 33 years or 9.6 million kilometers requirements. In this study, the applicability of aluminum alloy box is analyzed. The results show that both the aluminum ductile iron and the aluminum alloy can be used in metro gearboxes; both materials have their own advantages and disadvantages, and priority selection can be made during design based on the specific requirements of the vehicle.